Method for enhancing activity of gallic acid by using mesoporous Fe0 nano material and application of method

By fixing gallic acid in mesoporous zero-valent iron nanomaterial and encapsulating SiO2 to form Fe0@GA-ss-SiO2 nanomaterial, the problem of insufficient oxygen activation ability of gallic acid in tumor cells is solved, and its resistance is significantly enhanced Cancer activity achieves the effect of efficient ROS production in tumor cells.

CN119158040AActive Publication Date: 2024-12-20ANHUI UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411390280.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-08
Publication Date
2024-12-20
Estimated Expiration
2044-10-08

AI Technical Summary

Technical Problem

The existing technology is difficult to effectively enhance the anti-cancer activity of gallic acid, especially the lack of oxygen activation ability in tumor cells, resulting in poor treatment effect.

Method used

Fe0@GA-ss-SiO2 nanomaterial was prepared by immobilizing gallic acid in mesoporous zero-valent iron nanoparticles (Fe0 NPs) and encapsulating with a disulfide bond-containing SiO2 outer layer, which utilizes the strong reduction properties of Fe0 and The quinone derivatives of gallic acid work together to activate oxygen molecules to produce high levels of ROS and enhance anti-cancer activity.

Benefits of technology

At low doses, the oxygen activation ability of gallic acid is significantly improved, and it can produce high levels of ROS in tumor cells, induce tumor cell death, and significantly enhance the anti-cancer effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119158040A_ABST
    Figure CN119158040A_ABST
Patent Text Reader

Abstract

The invention discloses a method for enhancing the activity of gallic acid by using a mesoporous Fe0 nano material and application of the method. According to the invention, gallic acid (GA) with redox activity is fixed in mesoporous zero-valent iron nanoparticles (Fe0NPs), and then the mesoporous zero-valent iron nanoparticles (Fe0NPs) are encapsulated by a SiO2 outer layer (represented as Fe0atGA-s-SiO2NPs) containing disulfide bonds. Under the help of glutathione in cells, oxygen molecules are activated through electron transfer, a large amount of O2 <.-> and H2O2 are spontaneously generated, and Fe2 + with continuous high concentration derived from Fe0 further catalyzes H2O2 decomposition to generate highly oxidized. OH free radicals. Meanwhile, the GA quinone derivative generates < 1 > O < 2 > through a Russel Melanism mechanism, and < 1 > O < 2 > is generated through the Russel Melanism. An in-vitro cell experiment proves that the nano material can cause ferroptosis of cancer cells and shows an efficient cancer cell killing effect under an ultra-low dosage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of biomedicine technology and specifically relates to a method for 0 Methods and applications of nanomaterials to enhance the activity of gallic acid. Background Art

[0002] Gallic acid is a polyphenolic organic compound that is ubiquitous in plants in nature and is safe and beneficial to organisms. Polyphenol species have many potential health benefits. There is ample evidence that specific polyphenols produce many beneficial effects through their antioxidant activity, protecting the body from a variety of diseases, such as cancer and cardiovascular disease. Among them, gallic acid is a key bioactive ingredient in green tea. Gallic acid extracted from tea leaves has been shown to have a variety of biological and pharmaceutical functions, such as anti-fatigue, antibacterial, anti-cancer and inhibition of angiogenesis. The quinone and semiquinone species formed by the self-oxidation of gallic acid have the function of accelerating electron transfer in the process of electron transfer. At the same time, the quinone species formed can convert H2O2 into 1 O2 (Equation 1).

[0003] Chemodynamic therapy (CDT) is a new cancer treatment method in recent years. CDT uses the Fenton reaction with ferrous ions as catalysts to convert H2O2 into highly oxidized ·OH (Equation 2). Among the common ROS, ·OH has the strongest oxidizing ability (E(·OH / H2O) = 2.80V, E( 1 O2 / H2O)=2.17V,E(H2O2 / H2O)=1.78V), the Fenton reaction has been shown to be an effective strategy to induce cancer cell death by utilizing the high levels of endogenous hydrogen peroxide expressed in most tumors. 0 ) material as a carrier of GA, which can activate oxygen molecules as electron donors to produce a large amount of H2O2 (Equation 3), and the released Fe 2+ It can efficiently generate ·OH through the Fenton reaction. It is worth noting that gallic acid reacts with ferrous ions (Fe 2+ ) is the key chemical reaction in the preparation of ink, forming a blue-purple iron-gallic acid (Fe-GA) metal complex. Interestingly, this iron coordination compound has a high degree of reducing property. It can donate electrons from the gallic acid ligand to the surrounding free oxygen molecules, reducing oxygen (O2) to superoxide anions (O2 ·-) and hydrogen peroxide (H2O2) (Equation 4), which increases the content of H2O2 in the tumor, produces a large amount of ·OH inside the tumor, and induces ferroptosis. Ferroptosis is a necrotic cell death method catalyzed by ferrous ions. Its characteristic is that when the intracellular reduction system is inactivated, the lipid molecules containing polyunsaturated fatty acids located on the intracellular membrane structure are oxidized by reactive oxygen species (ROS). The accumulation of lipid peroxides eventually causes cell membrane rupture and increases the level of ROS in tumor cells to induce tumor cell death.

[0004] Q+2H2O2→Q+2H2O+ 1 O2 (1)

[0005] Fe 2+ +H2O2→Fe 3+ + OH+OH - (2)

[0006] O2+Fe 0 +2H + →Fe 2+ +H2O2 (3)

[0007] O2+Fe-GA+2H + →Fe-GA+H2O2 (4)

[0008] The inventor conducted the following search on the relevant contents of this application:

[0009] 1. Search results from http: / / scholar.glgoo.com / : (2024 / 01 / 24)

[0010] Search keywords Search Results <![CDATA[Patent Fe 0 Enhanced Anticancer Activity of Gallic Acid]]> none <![CDATA[Patented gallic acid-modified Fe 0 nanoparticles]]> none Gallic acid promotes the generation of reactive oxygen species none

[0011] 2. CNKI search results: (2024 / 01 / 24)

[0012] Search method 1:

[0013] Title-----Fe 0 Enhanced the anticancer activity of gallic acid.

[0014] Title-----Gallic acid modified Fe 0 Nanoparticles 0 items.

[0015] Title-----Promoting gallic acid-mediated singlet oxygen generation 0 items.

[0016] Search method 2:

[0017] Full text-----Fe 0 Enhanced the anticancer activity of gallic acid.

[0018] Full text-----Gallic acid modified Fe 0 There are 11 items of nanoparticles, none of which are relevant to this method.

[0019] Full text -----Promoting gallic acid-mediated singlet oxygen generation 1014 items, none of which are relevant to this method.

[0020] Search method three:

[0021] Keyword----Gallic acid 4200 items, none of which are relevant to this method.

[0022] Keyword----Oxygen activation efficiency 19 items, none of which are relevant to this method.

[0023] Keyword---singlet oxygen 954 items, none of which are relevant to this method. Summary of the invention

[0024] In view of this, the present invention aims to provide a method for utilizing mesoporous Fe 0 Methods and applications of nanomaterials to enhance the activity of gallic acid.

[0025] Nano-Zero-Valent Iron (Fe 0 ) has a strong reducing property, which enables it to act as an electron donor to activate molecular oxygen and produce a large amount of ROS. 2+ ) formed a blue-purple iron-gallate (Fe 3+ -GA) metal complex, this iron coordination compound is also highly reducing, it can donate electrons from the gallate ligand to the surrounding free oxygen molecules, reducing oxygen (O2) to superoxide anions (O2 ·- ) and hydrogen peroxide (H2O2). 0 and Fe 3+ -GA activated oxygen to generate H2O2, and the quinone derivative of gallic acid was converted into H2O2 by Russel Machinesm 1 O2. The synergistic effect of the two activates the anti-cancer ability of gallic acid. More importantly, this inorganic-organic hybrid nanomaterial also has excellent oxygen activation ability under the premise of low-dose application. Therefore, the present invention introduces GA into Fe 0 The porous structure of gallic acid was enhanced to achieve the anticancer activity of gallic acid.

[0026] The present invention utilizes mesoporous Fe 0 A method for enhancing the activity of gallic acid by nanomaterials is proposed by immobilizing gallic acid (GA) with redox activity on mesoporous zero-valent iron nanoparticles (Fe 0NPs), and then encapsulated by an SiO2 outer layer containing disulfide bonds to obtain Fe 0 @GA-ss-SiO2 nanomaterial.

[0027] The specific steps include:

[0028] Step 1: Monodisperse Fe 0 Preparation of Nanomaterials

[0029] Under N2 atmosphere, add dilute sulfuric acid solution (pH = 2.31 ± 0.02) to the three-necked flask reactor; weigh 20.1 mg of ferrous sulfate heptahydrate and 76 mg of hexadecyltrimethylammonium bromide, dissolve them fully with dilute sulfuric acid solution (pH = 2.31 ± 0.02) by ultrasonic assistance, add them to the reactor, and stir and disperse them evenly; weigh 14.5 mg of sodium borohydride, dissolve them fully with dilute sulfuric acid solution (pH = 2.31 ± 0.02), add them dropwise to the three-necked flask, the solution in the flask quickly turns black, continue to stir and disperse for 3 minutes, take out the black solution in the three-necked flask, immediately centrifuge and collect the precipitate, wash it with anhydrous ethanol 3 times, and vacuum dry it at room temperature to obtain black Fe 0 Nanomaterials. The Fe prepared in this step 0 Nanomaterials have a size of about 40nm-60nm.

[0030] Step 2: Monodisperse Fe 0 Preparation of @GA nanomaterials

[0031] 2.4 mg Fe 0 and 16 mg GA were dissolved in 5 mL of anhydrous ethanol, respectively, and recorded as solution 1 and solution 2. After ultrasonic dispersion, solution 1 was slowly dripped into solution 2, and the reaction was stirred magnetically for 6 h at room temperature. After the reaction, the precipitate was immediately centrifuged and collected, washed with anhydrous ethanol, and dried in vacuum at room temperature to obtain black Fe 0 @GA Nanomaterials.

[0032] Step 3: Monodisperse Fe 0 Preparation of @GA-ss-SiO2 nanomaterials

[0033] Weigh 5mgFe 0 @GA nanomaterials and 5mg DSPE-mPEG 2000Add to a glass bottle, add anhydrous ethanol to the glass bottle, ultrasonically disperse evenly, add 3.75mL deionized water and 400μL ammonia water (5.38mol / L) to the glass bottle, ultrasonically disperse evenly, take 3.5μL tetraethyl silicate (TEOS) and 1.4μL bis-[3-(triethoxysilyl)propyl]-disulfide (BTSPD) and add to the glass bottle, ultrasonically for 5min, add 0.2μL bis-[3-(triethoxysilyl)propyl]-tetrasulfide (BTESPD), and ultrasonically react for 2h; after the reaction is completed, immediately centrifuge and collect the precipitate, wash with anhydrous ethanol, and dry in vacuum at room temperature to obtain Fe 0 @GA-ss-SiO2 nanomaterial.

[0034] The present invention uses a SiO2 shell containing disulfide bonds to Fe 0 @GA nanomaterials are coated to increase Fe 0 The biocompatibility of @GA nanomaterials and the purpose of specific response to cancer cells in subsequent tumor treatment. The present invention optimizes the ratio of silicon source and sulfur source to finally determine the above parameters to ensure that a silicon dioxide shell layer with a suitable thickness is obtained after encapsulation.

[0035] In addition, the present invention uses an equal amount of Fe 0 Nanomaterials replace Fe 0 @GA nanomaterials, preparation of Fe 0 -ss-SiO2 nanomaterials for comparative investigation.

[0036] Fe of the present invention 0 @Application of GA-ss-SiO2 nanomaterials in the preparation of drug preparations for treating tumors.

[0037] Fe of the present invention 0 @Application of GA-ss-SiO2 nanomaterials in the preparation of ROS inducers.

[0038] Fe of the present invention 0 @GA-ss-SiO2 nanomaterials can specifically respond to the tumor microenvironment and produce high levels of ROS in tumor cells.

[0039] The present invention is based on mesoporous Fe 0 The reason why gallic acid is introduced into nanomaterials and has good ROS generation ability is that Fe 0 The anticancer activity of gallic acid is enhanced mainly through the following three pathways:

[0040] Path 1: Fe 0 The strong reducing property of pyrochlorein enables it to act as an electron donor to activate molecular oxygen and produce a large amount of ROS.

[0041] Pathway 2: Gallic acid and ferrous ions (Fe2+ ) forms a blue-purple iron-gallic acid (GA-Fe) metal complex. This iron coordination compound has a high degree of reducing ability. It can donate electrons from the gallic acid ligand to the surrounding free oxygen molecules, reducing oxygen (O2) to superoxide anions (O2 ·- ) and hydrogen peroxide (H2O2).

[0042] Pathway 3: The quinone derivatives formed by gallic acid self-oxidation have the function of accelerating electron transfer in the process of electron transfer. At the same time, the quinone derivatives formed can convert H2O2 into 1 O2.

[0043] Fe 0 @GA nanomaterials have high Fe 0 content and stronger ROS generation ability, and Fe 0 After the @GA nanomaterial is encapsulated by SiO2 containing disulfide bonds, gallic acid can produce a large amount of reactive oxygen species in the cells with the help of carriers, induce the accumulation of lipid peroxides in the cells, and effectively promote the iron death of tumor cells.

[0044] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0045] 1. The present invention utilizes Fe 0 The porous morphology of the nanomaterials introduces gallic acid into them, cleverly stimulating the anti-cancer potential of gallic acid.

[0046] 2. Fe of the present invention 0 @GA-ss-SiO2 nanomaterials have the potential to act as efficient ROS generators in the tumor microenvironment. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Figure 1 It is Fe 0 @Elemental mapping of GA-ss-SiO2 nanomaterials. Figure 1 It shows that the elements (O, N, Si, S) in the nanomaterial are evenly distributed, proving that Fe 0 @The successful synthesis of GA-ss-SiO2 nanomaterials.

[0048] Figure 2 It is the precursor Fe 0 Nanomaterials, final product Fe 0 @GA nanomaterials, Fourier transform infrared spectroscopy (FTIR) of GA (gallic acid). Figure 2 As shown, for Fe 0 @GANPs and Fe 0The Fourier transform infrared (FTIR) spectra of NPs were compared at 1540 cm -1 Near the absorption peak of GA ( The additional absorption peaks corresponding to the stretching vibrations indicate that GA is grafted onto Fe 0 NPs. It is worth noting that in Fe 0 @GANPs, GA 1028cm -1 The absorption peak (C-OH stretching vibration of carboxyl group) red-shifted to 1080 cm -1 , indicating that GA coordinates with iron. This proves that gallic acid successfully modifies Fe 0 Nanomaterials.

[0049] Figure 3 It is the precursor Fe 0 Nanomaterials (left), final product Fe 0 @GA nanomaterial (right) 10nm deep X-ray photoelectron spectroscopy (XPS). Figure 3 It can be seen that Fe 0 Nanomaterials and Fe 0 @GA nanomaterials have high Fe 0 Content, and Fe 0 @GA Nanomaterials Fe 0 The results show that Fe 0 @GA nanomaterials Fe 0 Higher than Fe 0 Fe in Nanomaterials 0 content.

[0050] Figure 4 It uses high concentration MB to detect Fe 0 @UV-visible absorption spectrum of ROS produced by GA nanomaterials. Figure 4 The results showed that in the Fe 0 The absorbance of MB detected in the nanomaterial experimental group and GA experimental group decreased slightly, while in the Fe 0 The absorbance of MB detected in the @GA nanomaterial experimental group decreased significantly, and the degradation rate of MB was about 80% after 5 min, which indicated that Fe 0 @GA nanomaterials have excellent ROS generation capabilities.

[0051] Figure 5 ABDA was used as an indicator to further evaluate Fe 0 @GA nanomaterials singlet oxygen production ability experimental results diagram. ABDA 1 In the presence of O2, 1 O2 reacts to reduce the absorbance of ABDA. Figure 5 It can be seen that Fe0 @GA nanomaterial experimental group ABDA absorbance decreased, indicating that Fe 0 @GA nanomaterials have been produced 1 O2 capabilities.

[0052] Figure 6 The UV-visible absorption spectrum of MB degradation experiment using IPA (isopropyl alcohol) as ·OH scavenger was used to explore the Fe 0 @GA nanomaterials molecular oxygen activation products. Figure 6 It can be clearly seen that in the presence of IPA, the degradation of MB was significantly inhibited, indicating that Fe 0 @GA nanomaterials have ROS products including OH.

[0053] Figure 7 The UV-visible absorption spectrum of MB degradation experiment using CAT (catalase) as H2O2 scavenger was used to explore the Fe 0 @GA nanomaterials molecular oxygen activation products. Figure 7 It can be clearly seen that in the presence of CAT, the degradation of MB was significantly inhibited, indicating that Fe 0 @GA nanomaterials produce ROS products including H2O2.

[0054] Figure 8 SOD (superoxide anion dismutase) is used as O2 ·- UV-visible absorption spectra of MB degradation experiments with scavengers to explore the Fe 0 @GA nanomaterials molecular oxygen activation products. Figure 8 It can be clearly seen that in the presence of IPA, the degradation of MB was significantly inhibited, indicating that Fe 0 @GA nanomaterials ROS products exist in O2 ·- .

[0055] Fig. 9 and Fig.10 The free radical scavenger DMPO was used to capture OH and O2 ·- ESR test results. Fig. 9 and Fig.10 It can be seen that in the Fe 0 @GA nanomaterial experimental group has very strong DMPO- . 1:2:2:1 ESR signal of OH and DMPO-O2 ·- The sextet signal further indicates that Fe 0 @GA nanomaterials have ROS products including OH and O2 ·- .

[0056] Fig.11The free radical scavenger TEMP is used to capture 1 O2 ESR detection experimental results. Fig.11 It can be seen that in the Fe 0 The GA nanomaterial experimental group has a very strong 1:1:1 ESR signal, which further indicates that Fe 0 @GA nanomaterials have ROS products 1 O2.

[0057] Fig.12 The Fe with a suitable thickness of silica shell was finally obtained by optimizing the ratio of silicon source and sulfur source. 0 TEM images of @GA-ss-SiO2 nanomaterials. Figures ad are 32μL TEOS, 13μL BTSPD; 16μL TEOS, 6.5μL BTSPD; 8.0μL TEOS, 3.3μL BTSPD; 3.5μL TEOS, 1.4μL BTSPD. BTESPD is 0.2μL.

[0058] Fig.13 The confocal laser scanning microscope was used, with DCFH-DA as ROS detection probe, ROSRGEEN as H2O2 probe, HPF as ·OH detection probe, and SOSG as 1 O2 detection probe; DHE is used as O2 ·- Probe. Detect total intracellular ROS, H2O2, ·OH, 1 O2, O2 ·- The experimental results obtained by detection are shown in Figure 2. Fig.12 As shown, it can be clearly seen that in Fe 0 @GA-ss-SiO2 nanomaterials treated HepG2 cells (human liver cancer cells) showed obvious green, green, green, green, and red fluorescence in turn, indicating that Fe 0 @GA-ss-SiO2 can produce more total ROS, H2O2, ·OH, 1 O2, O2 ·- . DETAILED DESCRIPTION

[0059] The technical solution of the present invention is further analyzed and explained below through specific embodiments.

[0060] Example 1: Preparation of target product

[0061] 1. Fe 0 Preparation of Nanomaterials

[0062] Select a 100mL three-necked flask, add 41mL of dilute sulfuric acid solution (pH=2.31) into it, and stir it for 5min with a mechanical stirrer (300rpm / min) under N2 atmosphere; weigh 20.1mg of ferrous sulfate heptahydrate and 76mg of hexadecyltrimethylammonium bromide, dissolve them fully with dilute sulfuric acid solution (pH=2.31) with ultrasonic assistance, add them to the three-necked flask, and stir and disperse them evenly for 5min; weigh 14.5mg of sodium borohydride, dissolve them fully with 2mL of dilute sulfuric acid solution (pH=2.31), and add them dropwise to the three-necked flask. The solution in the flask quickly turns black. After continuing to stir and disperse for 3min, take out the black solution in the three-necked flask, immediately centrifuge (9000rpm, 30s) and collect the precipitate, wash it three times with anhydrous ethanol, and dry it in vacuum at room temperature for 8h to obtain black Fe 0 Nanomaterials.

[0063] 2. Fe 0 Preparation of @GA nanomaterials

[0064] Select a 10mL brown glass bottle and weigh 2.4mgFe 0 Nanomaterials and 16 mg of gallic acid were added, and then 10 mL of anhydrous ethanol was added to the glass bottle, ultrasonically dispersed evenly, and magnetically stirred for 6 h at room temperature. After the reaction, the precipitate was immediately centrifuged (9000 rpm, 30 s) and collected, and vacuum dried at room temperature for 8 h to obtain black Fe 0 @GA Nanomaterials.

[0065] 3. Fe 0 Preparation of @GA-ss-SiO2 nanomaterials

[0066] Weigh 5mgFe 0 @GA nanomaterials and 5mg DSPE-mPEG 2000 Add to a glass bottle, add anhydrous ethanol to the glass bottle, ultrasonically disperse evenly, add 3.75mL deionized water and 400μL ammonia water (5.38mol / L) to the glass bottle, ultrasonically disperse evenly, take 3.5μL tetraethyl silicate (TEOS) and 1.4μL bis-[3-(triethoxysilyl)propyl]-disulfide (BTSPD) and add to the glass bottle, ultrasonically for 5min, add 0.2μL bis-[3-(triethoxysilyl)propyl]-tetrasulfide (BTESPD), and ultrasonically react for 2h. After the reaction is completed, immediately centrifuge and collect the precipitate, wash it 3 times with anhydrous ethanol, and dry it in vacuum at room temperature to obtain Fe 0 @GA-ss-SiO2 nanomaterial.

[0067] 4. Fe 0 - Preparation of ss-SiO2 nanomaterials

[0068] Fe 0 -ss-SiO2 nanomaterial preparation method and Fe 0 The preparation method of GA-ss-SiO2 nanomaterials is similar. 0 Nanomaterials replace Fe 0 @GA nanomaterials, other experimental operations remain unchanged.

[0069] Example 2: Fe 0 @GA-ss-SiO2 nanomaterials oxidation activity enhancement verification

[0070] 1. MB degradation detection of ROS generation

[0071] Experimental group 1: Fe 0 Nanomaterials (200 μg / mL) and Fe 0 @GA nanomaterials (200 μg / mL) were dispersed in MB (15 μg / mL) solution, reacted for 5 min, centrifuged (10000 rpm, 1 min), and the supernatant was taken to detect the absorbance change near 660 nm by UV-visible spectroscopy to explore the effect of Fe 0 Degradation effect of MB solution after introducing gallic acid on nanomaterials.

[0072] To further explore the Fe 0 @GA nanomaterials were used to generate ROS species. Based on the above experiments, ROS scavengers such as isopropyl alcohol (IPA, 1 mL / 4 mL), superoxide dismutase (SOD, 250 μg / mL), and catalase (CAT, 1.25 mg / mL) were introduced, and the type of ROS produced was determined by observing the degradation of MB.

[0073] 2. ABDA detection 1 O2 generation

[0074] Prepare ABDA (2mM, DMSO) solution. Select a 10mL centrifuge tube, add 20uLA ABDA solution and 4mL MES (pH=6.5) solution and mix well, and react at room temperature in the dark. After 10 minutes, centrifuge (10000rpm, 1min) and take the supernatant to record the change of ultraviolet absorption intensity near 400nm.

[0075] 4. Electron spin resonance spectroscopy (ESR) detection of OH and O2 ·-

[0076] Using DMPO as the capture agent, the ROS generated were determined by ESR to be OH and O2 ·-(DMPO: 5,5-Dimethyl-1-pyrrolineN-oxide, 5,5-dimethyl-1-pyrroline-N-oxide, free radical scavenger; EPR: electron spin resonance spectroscopy), indicating that Fe 0 @GA nanomaterials have ROS products including OH and O2 ·- .

[0077] Example 3: Detection of intracellular ROS

[0078] DCFH-DA was used to detect the production of ROS in cells under different treatment conditions. HepG2 cells (37°C, 5% CO2) were cultured for 24 h and then treated with gallic acid (2.75 μg / mL), Fe 0 @GA-ss-SiO2 nanomaterials (50 μg / mL) and Fe 0 -ss-SiO2 nanomaterials (50 μg / mL) were incubated for 12 h, washed three times with PBS, and then DCFH-DA was added and incubated for 15 min, followed by washing three times with PBS, adding 1 mL of PBS, and observing fluorescence imaging with a laser confocal scanning microscope.

Claims

1. A method using mesoporous Fe 0 The method for enhancing the activity of gallic acid with nanomaterials is characterized by: Gallic acid with redox activity was fixed in mesoporous zero-valent iron nanoparticles and then encapsulated by an outer layer of SiO2 containing disulfide bonds to obtain Fe 0 @GA-ss-SiO2 nanomaterial.

2. The method according to claim 1, characterized in that The steps include: Step 1: Monodisperse Fe 0 Preparation of Nanomaterials Under N2 atmosphere, add dilute sulfuric acid solution to the three-necked flask reactor; weigh ferrous sulfate heptahydrate and hexadecyltrimethylammonium bromide, dissolve them fully with dilute sulfuric acid solution with ultrasonic assistance, add them to the reactor, and stir to disperse them evenly; weigh sodium borohydride, dissolve it fully with dilute sulfuric acid solution, and add it dropwise to the three-necked flask, the solution in the flask quickly turns black, continue to stir and disperse, take out the black solution in the three-necked flask, centrifuge and collect the precipitate, wash with anhydrous ethanol, and vacuum dry at room temperature to obtain black Fe 0 Nanomaterials; Step 2: Monodisperse Fe 0 Preparation of @GA nanomaterials Fe 0 and GA were dissolved in anhydrous ethanol, respectively, and recorded as solution 1 and solution 2; after ultrasonic dispersion, solution 1 was slowly dripped into solution 2, and the reaction was stirred magnetically for 6 h at room temperature. After the reaction, the precipitate was immediately centrifuged and collected, washed with anhydrous ethanol, and dried in vacuum at room temperature to obtain black Fe 0 @GA Nanomaterials; Step 3: Monodisperse Fe 0 Preparation of @GA-ss-SiO2 nanomaterials Weigh Fe 0 @GA nanomaterials and DSPE-mPEG 2000 Add to a glass bottle, add anhydrous ethanol to the glass bottle, ultrasonically disperse evenly, add deionized water and ammonia water to the glass bottle, ultrasonically disperse evenly, add tetraethyl silicate and bis-[3-(triethoxysilyl)propyl]-disulfide to the glass bottle, ultrasonically disperse evenly, add bis-[3-(triethoxysilyl)propyl]-tetrasulfide, and ultrasonically react for 2 hours; after the reaction, centrifuge and collect the precipitate, wash with anhydrous ethanol, and vacuum dry at room temperature to obtain Fe 0 @GA-ss-SiO2 nanomaterial.

3. The method according to claim 2, characterized in that: In step 1, the pH of the dilute sulfuric acid solution is 2.31±0.

02.

4. The method according to claim 2, characterized in that: In step 1, the mass ratio of ferrous sulfate heptahydrate to sodium borohydride is 1.386:

1.

5. The method according to claim 2, characterized in that: In step 1, the Fe 0 The size of nanomaterials is between 40nm and 60nm.

6. The method according to claim 2, characterized in that: In step 2, Fe 0 The added amount of is 2.4 mg, and the added amount of GA is 16 mg.

7. The method according to claim 2, characterized in that: In step 3, Fe 0 @GA nanomaterials and DSPE-mPEG 2000 The added amount was 5 mg.

8. The method according to claim 7, characterized in that: In step 3, the amount of tetraethyl silicate added was 3.5 μL, the amount of bis-[3-(triethoxysilyl)propyl]-disulfide added was 1.4 μL, and the amount of bis-[3-(triethoxysilyl)propyl]-tetrasulfide added was 0.2 μL.

9. Fe prepared by any one of the preparation methods of claims 1 to 8 0 @Application of GA-ss-SiO2 nanomaterials in the preparation of drug preparations for treating tumors.

10. Fe prepared by any one of the preparation methods of claims 1 to 8 0 @Application of GA-ss-SiO2 nanomaterials in the preparation of ROS inducers.

Citation Information

Patent Citations

  • Method for chemically regulating and controlling dispersion degree and particle diameter of nanometer ferroferric oxide on basis of gallic acid-metal ion coordination

    CN107522239A

  • Method for effectively removing hexavalent chromium by using pyrogallic acid modified nano zero-valent iron synthesized by titration method

    CN115304149A

  • Method for improving oxygen activation efficiency by using metformin modified Fe &lt; 0 &gt; nano material

    CN117816956A

  • Preparation method and application of nano zero-valent iron cluster particles

    CN118598326A

  • Method for recovering reactivity of inactivated NANO zero-valent iron

    KR1020150009365A